2017
DOI: 10.1175/jcli-d-17-0159.1
|View full text |Cite
|
Sign up to set email alerts
|

Scale Dependence of Midlatitude Air–Sea Interaction

Abstract: It has traditionally been thought that midlatitude sea surface temperature (SST) variability is predominantly driven by variations in air–sea surface heat fluxes (SHFs) associated with synoptic weather variability. Here it is shown that in regions marked by the highest climatological SST gradients and SHF loss to the atmosphere, the variability in SST and SHF at monthly and longer time scales is driven by internal ocean processes, termed here “oceanic weather.” This is shown within the context of an energy bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
191
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(214 citation statements)
references
References 24 publications
21
191
2
Order By: Relevance
“…A recent study by Ma et al () reveals that the oceanic mesoscale eddy‐atmosphere (OMEA) interaction is an important yet previously overlooked component in the mesoscale eddy dissipation. At mesoscales, sea surface temperature anomaly (SSTA) tends to be positively correlated with heat flux (HF; defined positive upward) anomaly (HFA) due to the dominance of HF induced by oceanic eddies to atmospheric forcing (Bishop et al, ; Ma et al, ). This leads to the destruction of eddy potential energy (EPE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Ma et al () reveals that the oceanic mesoscale eddy‐atmosphere (OMEA) interaction is an important yet previously overlooked component in the mesoscale eddy dissipation. At mesoscales, sea surface temperature anomaly (SSTA) tends to be positively correlated with heat flux (HF; defined positive upward) anomaly (HFA) due to the dominance of HF induced by oceanic eddies to atmospheric forcing (Bishop et al, ; Ma et al, ). This leads to the destruction of eddy potential energy (EPE).…”
Section: Introductionmentioning
confidence: 99%
“…S. Smith, 2007), whereas their energy pathway to dissipation has not been completely understood (Ferrari & Wunsch, 2009;Wunsch & Ferrari, 2004). surface temperature anomaly (SSTA) tends to be positively correlated with heat flux (HF; defined positive upward) anomaly (HFA) due to the dominance of HF induced by oceanic eddies to atmospheric forcing (Bishop et al, 2017;Ma et al, 2016). This leads to the destruction of eddy potential energy (EPE).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, there has been a steadily growing body of evidence suggesting that ocean mesoscale and frontal-scale features in the Kuroshio Extension (KE) and Gulf Stream (GS) regions are forcing the atmosphere (e.g., Chelton et al, 2004;Kuwano-Yoshida & Minobe, 2017;Ma et al, 2016;Piazza et al, 2016;Seo et al, 2017;Small et al, 2014;Xie, 2004). In particular, a positive correlation between sea surface temperature (SST) and near-surface wind speed over western boundary currents (WBCs) suggest an ocean-toatmosphere forcing through turbulent heat fluxes (Nonaka & Xie, 2003), whose variability on monthly and longer timescales is largely driven by internal ocean processes (Bishop et al, 2017). Studies considering the atmospheric impact of WBCs typically fall into one of two broad categories-the oceanic impact on the mean state (e.g., Shimada & Minobe, 2011) and on synoptic storms (e.g., Hirata et al, 2015Hirata et al, , 2018, with community efforts still very much ongoing (e.g., Nkwinkwa Njouodo et al, 2018;Small et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the western boundary current and its extension, such as the Kuroshio Extension (KE), energetic ocean mesoscale eddies and fronts contribute greatly to mesoscale sea surface temperature (SST) variability (Chelton et al, 2004;Xie, 2004;Small et al, 2008;Bryan et al, 2010;Neill et al, 2012;Bishop et al, 2017). The mesoscale SST anomaly (SSTA) is tightly coupled with the atmosphere (Minobe et al, 2008;Ma et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The mesoscale SST anomaly (SSTA) is tightly coupled with the atmosphere (Minobe et al, 2008;Ma et al, 2016b). Previous studies using high-resolution satellite observations and numerical models showed that it is the ocean that drives the atmosphere at the mesoscale (e.g., Bryan et al, 2010;Chelton and Xie, 2010;Frenger et al, 2013;Ma et al, 2016a;Bishop et al, 2017).…”
Section: Introductionmentioning
confidence: 99%